Analisis Pernyataan Misi, Permasalahan DanKinerja Ekspor Indonesia - Ardiyanti, Yuri, Dr.Agung Riyardi M.si (2017)
This study, entitled "Mission Statement Analysis, Problems and Indonesian Export Performance". The purpose of this study to analyze the mission statement of the Directorate General of Export Development,to analyze the problems in exports, and to analyze the performance of exports in Indonesia linked to the national income to determine the pattern or direction of causality between exports and GDP in Indonesia based on the period of time from 1985 - 2015. The research method associated with the object of the Faculty of Economics and Business University Muhammadiyah of Surakarta, Department of Trade Surakarta, Industry trangsan rattan of Sukoharjo. The data used are primary data in the form of the questionnaire data mission statement, readability level Directorate General of Export Development and problems of exports in Indonesia, while the secondary data, exports and GDP in Indonesia, the analytical methods used for primary data,qualitative and descriptive, while secondary data uses Sims causality test is to determine whether export affect national income and national income affect exports. The results of this study can be concluded that the content of the mission statement has great results with a component that is often used is the geographic market with a readability result is legible optimal by showing writing style is clear and concise in wording and sentences but need to revisit the mission statement by reducing the length sentences and use. The results indicated that the export concerns the export of raw minerals which an export problem has a very important priority in doing discussion, while for secondary data concluded that the positive effect of stationary variable export to GDP while GDP variable stationary positive effect on exports in Indonesia.